Introduction to systems analysis and design 4th edition - Hawryszkiewycz Igor (Prentice Hall of India, New Delhi, 2004)
Stats/Maths
ENGLISH
Keywords: Introduction to systems analysis and design 4th edition; Stats/Maths; Stats/Maths